2011
DOI: 10.1606/1044-3894.4155
|View full text |Cite
|
Sign up to set email alerts
|

What Couples who Adopt Children from Child Welfare Want Professionals to Know about Supporting Their Marriages

Abstract: This article provides suggestions for supporting the marriages of couples who adopt children from the child welfare system. These suggestions emerged from qualitative data obtained from 22 spouses in 4 focus groups. Data reveal that couples want professionals to address the impact of adoption on the marital relationship prior to placement of children, to facilitate contact among adoptive couples that focuses on couple relationships in addition to parenting issues after children have been placed, and to activel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…That is, rather than reacting to problems after the fact, we argue that it is imperative to provide CWPs with basic RME knowledge, tools, and skills so they 1) can recognize opportunities to provide RME, 2) are ready and able, when needed, to help strengthen couple and/ or coparenting relationships, or 3) can understand when the situation better warrants a referral to FLE or counseling services. Recently, scholars have reinforced that integrating RME with services that CWPs provide may be especially desirable and beneficial to home visitation programs , foster and adoptive parents (Mooradian, Hock, Jackson, & Timm, 2011) and youth aging out of the foster care system (Antle, Johnson, Barbee, & Sullivan, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, rather than reacting to problems after the fact, we argue that it is imperative to provide CWPs with basic RME knowledge, tools, and skills so they 1) can recognize opportunities to provide RME, 2) are ready and able, when needed, to help strengthen couple and/ or coparenting relationships, or 3) can understand when the situation better warrants a referral to FLE or counseling services. Recently, scholars have reinforced that integrating RME with services that CWPs provide may be especially desirable and beneficial to home visitation programs , foster and adoptive parents (Mooradian, Hock, Jackson, & Timm, 2011) and youth aging out of the foster care system (Antle, Johnson, Barbee, & Sullivan, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in recent years, RME programs are being implemented at the individual level in schools, correctional facilities, domestic violence shelters, rehabilitation clinics, and other agencies that provide social services (Hawkins, 2012). Taken together, individuals, couples, and families in the child welfare system may be open to receiving RME, including foster youth (Antle et al, 2009) and adopting parents (Mooradian et al, 2011), and training CWPs in relationship principles and skills could be an ideal delivery system, as low-resource families may be less likely to attend group RME programs .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the need for and interest in RME (Mooradian et al, 2011;Sar et al, 2010), integrating RME into child welfare services remains a controversial matter because of the lack of awareness regarding the relevance and benefits of RME to child welfare as well as the perceived barriers inherent in implementing RME Schramm et al, 2013). As such, the development process began with identifying and exploring the problem (e.g., relevance of RME to child welfare clients, interest from and potential barriers to CWPs employing RME) in order to inform a well-reasoned theory of change that could be implemented and tested.…”
Section: Discussionmentioning
confidence: 99%
“…Antle, Frey, Sar, Barbee, and van Zyl (2010) have noted that strengthening couples and families could serve as both a primary prevention strategy for foster and kinship care providers whose relationship might be taxed following a placement of a child in their home, and as a secondary prevention strategy for families already in the child welfare system by strengthening the couple relationship and thus minimizing the negative spillover effects of couple conflict on children. Research has shown that, in addition to client interest (Mooradian, Hock, Jackson, & Timm, 2011), child welfare professionals (CWPs) believe that RME is both relevant and appropriate for the work they perform (Sar, Antle, Bledsoe, Barbee & van Zyl, 2010;Schramm, Futris, Galovan, & Allen, 2013) and that training can facilitate positive shifts in attitudes that could facilitate the integration of RME into child welfare programming . As the field of child welfare expands its focus to preventive services and includes trainings on ''controversial topics'' such as RME, it is critical that evaluation models assess the effectiveness of such trainings.…”
mentioning
confidence: 99%
“…In a qualitative study, Mooradian, Hock, Jackson, and Timm (2011) used a focus group approach to ask couples who had adopted children from the child welfare system about how professionals could support their marriages. The couples expressed a strong need to have interaction with other adoptive couples facing similar family situations.…”
Section: Support Network and Marriage Enhancementmentioning
confidence: 99%